Cardiovascular and cardioprotective effects of Gomphrena perennis L. (Amaranthaceae) dye tincture in rats - Bonilla Bonilla, Adriana Milena (2017)
Gomphrena perennis L. (Amaranthaceae) is a South American plant. In Argentine it is widely used as emollient, diuretic, hypotensive and for cardiac diseases. We previously demonstrated its antispasmodic effect on rat duodenum. This work evaluated the effects of Gomphrena tincture (GphT) on the contractile and energetic recovery of isolated rat hearts exposed to a model of stunning due to ischemia and reperfusion (I/R) as well as on the blood pressure of normotensive rats. GphT was prepared by aceration of leaves at 20% in ethanol 70°. Rats were anesthetized with 1.5g/kg urethane via i.p. and placed in a supine position with tracheal cannulation. Blood pressure (BP) was directly measured through an heparinized cannula in the internal carotid artery connected to a pressure transducer. To evaluate whether the GphT have a direct effect on hearts by an ischemic insult, isolated rat hearts were perfused at 37°C with control Krebs (C) in the chamber of a flow-calorimeter. After a 30-min equilibration period, the following protocols were done on each heart: perfusion with 0.1, 0.3 and 0.5% v/v GphT, followed by exposition to no-flow ischemia (I) during 20 min and to R with Krebs during 45 min. The contractility was evaluated from the left intraventricular pressure (P) which was measured simultaneously with the total heat rate (Ht) released by the heart. Basal BP of normotensive rats was 70.2 ± 15.2 mm Hg (n=4). GphT induced a dose-dependent hypotension (ΔBP: -13.6 ± 6.0 and -28.2 ± 11.6 mmHg respectively for 0.5% and 2% GphT, n=4). ΔBP was significantly reversed by the pre-treatment with L-NAME. Heart rate (HR) was not significantly modified by GphT at any dose, as neither after L-NAME. Perfusion of GphT in hearts produced a concentration-dependent positive inotropism. Nevertheless, 0.1% GphT significantly reduced cardiac contractility (P) and total muscle economy (Eco = P/Ht), as well as induced a diastolic contracture during R. The results suggest that: 1- The i.p. administration of GphT produced a dose dependent transitory hypotension and this effect was mediated by release of NO from the NO-synthase; 2- GphT induced a positive inotropism but increased the stunning of hearts exposed to I/R.